IMPLEMENTASI HASIL MUSYAWARAH PERENCANAAN PEMBANGUNAN TAHUN 2022 DI KELURAHAN NAMBO JAYA KECAMATAN KARAWACI KOTA TANGERANG - Sukirno, Sukirno; Khikmawanto, Khikmawanto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research aims to analyze the implementation of the results of the Development Plan Deliberation in Nambo Jaya Village, Karawaci District, Tangerang City. The theoretical concept used to carry out the analysis is related to George Edward's implementation theory using communication, resources, disposition and bureaucratic structure variables. As a result of this research, information was obtained that budget limitations were one of the causes of the failure to realize 75 proposals from the development planning deliberation. Determining the priority scale is not determined by the urgency and needs of the community but is determined by budget limitations, so that the results of the verification carried out by the Public Works and Spatial Planning Service and the Tangerang City Regional Development Planning Agency are only 2 proposals resulting from the Musrenbang which will be realized in 2023 for the construction of road infrastructure. environment and development of the Sabi River Retaining Sheet. The budget allocation for activities resulting from development plan deliberations is IDR. 3,000,000,000,- for the realization of two proposals, namely improving environmental roads and building sheet piles for Sabi River